Maximal lipidic power in high competitive level triathletes and cyclists. Issue 1 (24th October 2006) - González-Haro, C; Galilea, P A; González-de-Suso, J M; Drobnic, F; Escanero, J F
Abstract : Objective: To describe the fat-oxidation rate in triathlon and different modalities of endurance cycling. Methods: 34 endurance athletes (15 male triathletes, 4 female triathletes, 11 road cyclists and 4 male mountain bikers) underwent a progressive cycloergometer test until exhaustion. Relative work intensity (VO2max ), minimal lactate concentration (La − min ), lactic threshold, individual lactic threshold (ILT), maximal fat-oxidation rate (Fatmax, Fatmax zone) and minimal fat-oxidation rate (Fatmin ) were determined in each of the groups and were compared by means of one-way analysis of variance. Results: No significant differences were found for Fatmax, Fatmin or for the Fatmax zone expressed as fat oxidation rate (g/min). Intensities −20%, −10% and −5% Fatmax were significantly lower for mountain bikers with respect to road cyclists and female triathletes, expressed as % VO2max . Intensities 20%, 10% and 5% Fatmax were significantly lower for mountain bikers with respect to male triathletes and female triathletes, and for male triathletes in comparison with female triathletes, expressed as % VO2max . Lactic threshold and La − min did not show significant differences with respect to Fatmax . Lactic threshold was found at the same VO2max with respect to the higher part of the Fatmax zone, and La − min at the same VO2max with respect to the lower part of the Fatmax zone. Conclusions: The VO2max of Fatmax and the Fatmax zone may explain the different endurance adaptations of the athletes according to their sporting discipline. Lactic threshold and La − min were found at different relative work intensities with respect to those of Fatmax even though they belonged to the Fatmax zone.